Sustainable Development Management of Regional Hospitality Industry: Synergy of Economic Policy and Local Strategies - Harbar, Halina; Banyeva, Iryna; Ivanenko, Tetiana; Kushniruk, Viktor; Pavliuk, Svitlana (Journal of Environmental Accounting and Management, 2026)
The aim of the study was to identify the patterns of interrelation between economic policy, local development strategies of tourism and the hotel industry of the Southern region of Ukraine, in particular Odesa and Mykolaiv regions, in the context of ensuring sustainable development and increasing the competitiveness of the hospitality industry. The methodology was based on a combination of analysis of official statistical data, macroeconomic indicators, and practical case studies of tourism enterprises’ operations. As a result of the study, a number of quantitative indicators were obtained that reflect the dynamics of the hospitality sector in 2020–2024. Thus, the number of hotel visitors in Mykolaiv region decreased from 42.1 thousand people in 2020 to 15.4 thousand in 2022; however, in 2024 the indicator recovered to 28.7 thousand, indicating a gradual recovery of tourist flows. At the same time, the revenues of the hotel and restaurant sector in the region fell by more than 40% in 2020–2022, and tax revenues decreased from UAH 18.2 million in 2020 to UAH 7.6 million in 2022, with a subsequent partial recovery to UAH 12.4 million in 2024. A more stable dynamic was recorded for Odesa region: in 2023, hotels in the region served about 280 thousand tourists, and total revenues exceeded UAH 1.1 billion, showing a 15% increase compared to 2022. The average profitability level of hospitality enterprises in Odesa ranged from 12% to 14%, while in Mykolaiv it remained at 7% to 9%, reflecting regional asymmetry of development. The results obtained summarise the development trends of the hospitality industry and have practical significance for formulating recommendations to optimise the management of the tourism sector of the Southern region to ensure sustainable growth and preserve its cultural and environmental potential.